Modified Moving-average Crossover Trading Strategy: Evidence in Malaysia Equity Market - Tapa, Afiruddin; Yean, Soh Chuen; Ahmad, Shahrul Nizam (International Journal of Economics and Financial Issues, 2016)
This study examined the profitability of technical analysis using moving-average (MA) crossover strategy compared with the conventional simple buy-and-hold strategy, using Malaysian equity market. We investigates the performance of the original moving-average strategy and a modified moving-average crossover strategy with additional trading rules such as entry rule, exit rule, holding rule, and stop-loss rule. The results are consistent to previous studies that strongly support moving-average crossover trading strategies. The result suggests that all combinations of short-MA and long-MA periods of the original MA crossover strategy and majority combinations of short-MA and long-MA of the modified MA crossover strategy outperform market benchmark with higher risk-adjusted return. In addition, the 1-period short-MA demonstrates the best return in both original and modified moving-average crossover strategy; better still the modified strategy outperforms the original strategy with lower frequency of trades which could largely reduce transaction costs and with lower return distribution variability. Keywords: Technical Analysis, Moving-Average Crossover, Trading Strategies JEL Classifications: G1, G12